Readability Analysis of Online Patient Educational Materials on Blepharoplasty. Issue 2 (June 2022) - Patel, Manish J.; Shah, Parth V.; Garg, Stuti P.; Cristel, Robert T.
Blepharoplasty is a common procedure for correction of eyelid appearance. Online educational material among surgical procedures is often written higher than the recommended fifth-grade level. The objective of this study is to evaluate the readability of online patient education materials (OPEMs) available on Google for patients interested in blepharoplasty. Using 6 different pre-established readability scores, the top 100 Google results on blepharoplasty were screened for analysis. A total of 87 OPEMs were found to be relevant yielding an average grade reading level of 11.90 (range 7-20; 95% confidence interval [CI], 11.45-12.33). In addition, OPEMs readability scores were not influenced by whether the author was a medical provider. This study demonstrated the average reading level for available information on blepharoplasty is higher than the recommended fifth-grade reading level. Readability is only one metric for evaluating comprehendible information; however, authors of online medical education need to be more conscious of the public's ability to comprehend and should tailor their content delivery appropriately.